Multi-omics study in monozygotic twins confirm the contribution of de novo mutation to psoriasis. Issue 106 (January 2020) - Li, Junqin; Lin, Haoxiang; Hou, Ruixia; Shen, Juan; Li, Xiaofang; Xing, Jianxiao; He, Fusheng; Wu, Xueli; Zhao, Xincheng; Sun, Liangdan; Fan, Xing; Niu, Xuping; et al.
Abstract: Background: Genome-wide association studies have identified over 120 risk loci for psoriasis. However, most of the variations are located in non-coding region with high frequency and small effect size. Pathogenetic variants are rarely reported except HLA-C*0602 with the odds ratio being approximately 4.0 in Chinese population. Although rare variations still account for a small proportion of phenotypic variances in complex diseases, their effect on phenotypes is large. Recently, more and more studies focus on the low-frequency functional variants and have achieved a certain amount of success. Method: Whole genome sequencing and sanger sequencing was performed on 8 MZ twin pairs discordant for psoriasis to scan and verified the de novo mutations (DNMs). Additionally, 665 individuals with about 20 years' medical history versus 2054 healthy controls and two published large population studies which had about 8 years' medical history (including 10, 727 cases versus 10, 582 controls) were applied to validate the enrichment of rare damaging mutations in two DNMs genes. Besides, to verify the pathogenicity of candidate DNM in C3, RNA-sequencing for CD4 +, CD8 + T cells of twins and lesion, non-lesion skin of psoriasis patients were carried out. Meanwhile, the enzyme-linked immunosorbent assay kit was used to detect the level of C3, C3b in the supernatant of peripheral blood. Result: A total of 27 DNMs between co-twins were identified. We found six of eight twins carry HLA-C∗0602 allele which have large effects on psoriasis. And it is interesting that a missense mutation in SPRED1 and a splice region mutation in C3 are found in the psoriasis individuals in the other two MZ twin pairs without carrying HLA-C*0602 allele. In the replication stage, we found 2 loss-of-function (LOF) variants of C3 only in 665 cases with about 20 years' medical history and gene-wise analysis in 665 cases and 2054 controls showed that the rare missense mutations in C3 were enriched in cases (OR = 1.91, P = 0.0028). We further scanned the LOF mutations of C3 in two published studies (about 8 years' medical history), and found one LOF mutation in the case without carrying HLA-C*0602. In the individual with DNM in C3, RNA sequencing showed the expression level of C3 in skin was significant higher than healthy samples in public database (TPM fold change = 1.40, P = 0.000181) and ELISA showed protein C3 in peripheral blood was higher ( 2.2-fold difference) than the other samples of twins without DNM in C3 . Conclusion: To the best of our knowledge, this is the first report that DNM in C3 is the likely pathological mutations, and it provided a better understanding of the genetic etiology of psoriasis and additional treatments for this disease. Highlights: Multi-omics difference of psoriasis dis-concordance monozygotic twins are compared . HLA allele which have large effects on psoriasis were observed on six of our twins . Loss-of-function variants of C3 are found in psoriasis. . De novo mutation is contributed to psoriasis. .